(untitled) (University of Khartoum Engineering Journal, 2022)
Digital elevation model (DEM) is a basic component of any geo-information system (GIS) and is required for many applications. The production of the worldwide DEMs has been improved with the production of ENVISAT-DEM. Extracting topographical data by drawing contour lines from ENVISAT-DEM elevation data therefore requires accuracy assessment of ENVISAT-DEM elevation data and cartographic quality of the interpolated contours to ensure its suitability for topographical mapping. This paper presents the results of accuracy tests which were performed for different types of topography. The overall ENVISAT-DEM R.M.S.E value was about ±6.785m (±4.926m excluding Habilla study area) which is less than the estimated range of R.M.S.E value (± 10m to ± 25m) specified by European Space Agency (ESA). The ENVISAT-DEM was found to contain significant anomalies and artifacts, which will affect its usefulness for user applications. ENVISAT-DEMs may be one of the best global sources of elevation data for topographic mapping at 1:50000 scales or less if further processing and improvements are applied to remove blunders and outliers.